Comunicação interna em empresas públicas: o caso dos Correios - Almeida, André Luiz de Oliveira (2024)
This dissertation aimed to investigate how internal communication is structured in a public company, what strategies are used and what employees' perception is regarding this process. The study also aims to analyze the role of informal networks and propose improvements in the internal communication process of a public company at the federal level. The construction of this *work* encompasses a bibliographic review of theories on internal communication and organizational communication, based on authors such as Scroferneker (2000), Kunsch (2016), Matos (2004) and Curvello (2012), and carrying out an in-depth interview with some company employees. The methodological strategy used was the case study. The study is also characterized as an applied research, with a qualitative approach, with in-depth interviews carried out with employees of the company researched. The data collected in this research were analyzed using the thematic analysis technique and the results demonstrate that the company's internal communication is focused on channels such as the intranet and corporate email and that, according to the perception of the interviewed employees, the process communication is carried out through relevant, known tools and achieves its objective. There is, however, a concern that excessive communication will discourage employees from reading, affecting the relevance of these tools. Another concern among employees is related to the officialization of WhatsApp as a valid tool for internal communication, since today it is already used informally.